PENGARUH ENVIRONMENTAL KNOWLEDGE DAN GREEN PERCEIVED VALUE TERHADAP PURCHASE INTENTION DI FORE COFFEE - Dwi Nuraini, Shofiyah; Puspita, Dela; Puspita Dewi, Olga; Andini Rosadi Putri, Reva; Fitria Salsabila, Najwa; Lestari Napitupulu, Rohani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the increasing problem of plastic waste that has an impact on the environment, social, and economy, where Indonesia is included in the top five countries contributing plastic waste to the sea. This condition encourages a number of companies, including Fore Coffee, to use environmentally friendly concepts through the use of reusable packaging. However, not all consumers make environmental factors a primary consideration in purchasing decisions, so it is necessary to study more deeply the factors that influence purchase intention towards environmentally friendly products. Therefore, this study aims to determine the effect of Environmental Knowledge and Green Perceived Value on Purchase Intention at Fore Coffee. The study used a quantitative method with data collection through questionnaires to 120 respondents, analyzed using data quality tests, classical assumption tests, multiple linear regression, and hypothesis testing through IBM SPSS Statistics 22. The results showed that Environmental Knowledge had no significant effect on Purchase Intention, while Green Perceived Value had a positive and significant effect. Thus, it is concluded that consumer perceptions of environmentally friendly values are more dominant in shaping purchase intention than environmental knowledge.